2015
DOI: 10.5713/ajas.14.0784
|View full text |Cite
|
Sign up to set email alerts
|

Y-Single Nucleotide Polymorphisms Diversity in Chinese Indigenous Horse

Abstract: In contrast to high genetic diversity of mitochondrial DNA (mtDNA), equine Y chromosome shows extremely low variability, implying limited patrilines in the domesticated horse. In this study, we applied direct sequencing and restriction fragment length polymorphism (RFLP) methods to investigate the polymorphisms of 33 Y chromosome specific loci in 304 Chinese indigenous horses from 13 breeds. Consequently, two Y-single nucleotide polymorphisms (SNPs) (Y-45701/997 and Y-50869) and one Y-indel (Y-45288) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The low MSY diversity cannot be explained by a low mutation rate; the Y chromosome lineages of modern horses are clearly distinct from those of the Przewalski's horse (E. przewalskii) [7], and prehistoric horses have much more diversity [8][9][10]. Rather, the presence of only six Y chromosome haplotypes (HTs) in modern European horse breeds [2] and the limited microsatellite variability [11][12][13] suggest an extremely low effective population size of males. The decline of Y chromosome diversity in horses likely started about 5,500 years ago with genetic bottlenecks during the domestication process [14,15] and was further enhanced by multiple prehistoric and historic waves of migration [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The low MSY diversity cannot be explained by a low mutation rate; the Y chromosome lineages of modern horses are clearly distinct from those of the Przewalski's horse (E. przewalskii) [7], and prehistoric horses have much more diversity [8][9][10]. Rather, the presence of only six Y chromosome haplotypes (HTs) in modern European horse breeds [2] and the limited microsatellite variability [11][12][13] suggest an extremely low effective population size of males. The decline of Y chromosome diversity in horses likely started about 5,500 years ago with genetic bottlenecks during the domestication process [14,15] and was further enhanced by multiple prehistoric and historic waves of migration [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…In horses, however, the assembly for the whole NRY region is not available yet, as the reference genome was characterized from a single mare individual (Wade et al 2009). Studies targeting specific NRY regions have shown limited variation, with haplotypes differing by one mutational step at best, which indicates that only a handful of paternal lines survived until present-day in domestic horses (Lindgren et al 2004;Brandariz-Fontes et al 2013;Wallner et al 2013;Kreutzmann et al 2014;Han et al 2015). By contrast, analyses initially based on the mtDNA control region (D-loop) (Lister et al 1998;Vilà et al 2001;Jansen et al 2002;Cieslak et al 2010), and more recently on complete mitochondrial genomes (Lippold et al 2011a;Achilli et al 2012), revealed horses as the domestic animal showing one of the largest pools of mitochondrial genetic diversity.…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%
“…The Chinese breeds could be divided into five major groups by genotyping these animals for 27 microsatellite loci [13]. Previous study had also shown that there were two haplotypes of Y chromosome discovered in the domestic horse breeds in China [16], which develop into an important tool for horse population genetics [17].…”
Section: Characters Of Jianchang Horse's Mitochondrial Genomementioning
confidence: 99%